Economic Evaluation of Sea Tourism with Travel Cost Method in the Romantic Beach of Serdang Bedagai, North Sumatra - Ginting, Dio Aginta; Darwis, Darwis; Yulinda, Eni (Jurnal Perikanan dan Kelautan, 2024)
Romantic Beach, located in Serdang Bedagai Regency, precisely in Nagalawan Perbaungan Village, North Sumatra, this beach is between Cemara Beach and Kampung Nipah Mangrove tourism, because this beach has very beautiful white sand and is located around a large mangrove forest, this Romantic Beach become a tourist spot. This research was conducted at Romantic Beach Tourism, Deli Serdang Regency, North Sumatra Province, in June 2023. This research aimed to look at the factors that influence the number of tourist visits to Romantic Beach and to determine the economic value of Romantic Beach The research method used in this research is a survey. The researcher goes directly into the field to obtain research data. The methods used in this research are the travel cost method and surveys by collecting primary data for analysis. The data analysis used is Descriptive Analysis. With this analysis, travel costs, income, distance, age, and education influence the number of romantic beach tourism visits. The economic value of Romantic Beach using the travel cost method approach is IDR 29,116,354.00 / year, the maximum cost incurred by respondents is IDR 750,000.00, and the minimum cost incurred by respondents is IDR 140,000.00